Embolization of splenic artery aneurysm associated with gastrointestinal bleeding: case report - Casas,André Luís Foroni (2014)
The splenic artery is the visceral vessel that is most often affected by aneurysmal disease. Occasionally, gastrointestinal bleeding may signify that the aneurysm is in communication with the digestive tract. We report on the case of a 64-year-old multiparous patient with intermittent digestive bleeding caused by a splenic artery aneurysm who was successfully treated with endovascular embolization.